2017
DOI: 10.1103/physrevb.95.214110
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent far-infrared reflectance of an epitaxial (BaTiO3)8/(SrTiO3)4 superlattice

Abstract: Infrared reflectance spectra of the polar optic phonons in a [(BaTiO3)8/(SrTiO3)4]50 superlattice over the temperature range 8 to 650 K are reported. The spectra exhibit lattice vibration features typical of the perovskite constituents, BaTiO3 and SrTiO3. Using the effective medium approximation for multilayers systems and a fitting procedure, we were able to successfully simulate the infrared reflectivity of the superlattice structures and extract the parameters and dielectric functions of the phonons. When a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Looking forward, alloy BVMD potentials not only enable the prediction of macroscopic (lattice constants, polarization, structure phase transitions, and their temperatures) and microscopic (Ti displacements) physical properties of technologically important ferroelectric perovskite alloys such as BST, BZT, PZT, and PMN-PT but also the nanoscale design of new materials via compositional tuning and heterostructure/superlattice engineering. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] Supplemental Material…”
Section: Discussionmentioning
confidence: 99%
“…Looking forward, alloy BVMD potentials not only enable the prediction of macroscopic (lattice constants, polarization, structure phase transitions, and their temperatures) and microscopic (Ti displacements) physical properties of technologically important ferroelectric perovskite alloys such as BST, BZT, PZT, and PMN-PT but also the nanoscale design of new materials via compositional tuning and heterostructure/superlattice engineering. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] Supplemental Material…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, the experimental information regarding symmetry of the STO m /BTO M−m superlattice varies considerably, mainly suggesting different STO phases, starting from tetragonal to orthorhombic (and monoclinic in the first principles calculations [29][30][31]. We limit our superlattice model to the tetragonal symmetry as suggested in recent experiment studies [12][13][14] and develop a model on the basis of the space-group symmetry relations.…”
Section: Superlattice Modelsmentioning
confidence: 99%
“…It was also demonstrated that the tetragonal phase for STO 10 /BTO 10 superlattice remains stable down to 77 K, while the phase transition to the paraelectric state is diffused and shifted up to T c = 650 − 700 K 25 . Lastly, the very recent study 14 claims that strained [STO 4 /BTO 8 ] 50 superlattice on the DyScO 3 (110) has the tetragonal P4mm symmetry below 550 K (another phase transition between 200 and 300 K was also suggested 14 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations